Metode Penyembuhan Melalui Ajaran Pembenaran Oleh Iman - Richard Jimmy Irawan; Rudolf W. Sagala; A. Hendriks; Rolyana Ferinia (Peneliti.net, 2023)
The purpose of this research is to find out how the healing method that Jesus used during His ministry in this world, and to examine the relevance of His healing method in today's times, and to analyze the extent to which the doctrine of justification by faith is able to provide a solution for healing the diseases for church members and also as a tool to prevent the church members from disease. This research is a writing that is produced through a literature review by researchers who are described descriptively. Through this research it was found that the method that Jesus used during His ministry shows that the faith of the sufferer determines his healing, not only physically but also mentally and spiritually. The relevance of the healing method that Jesus used in the New Testament era to today is still very influential which is mixed through the doctrine of justification by faith. The doctrine of Justification by faith is not only able to heal sufferers but is also effective in preventing church members from suffering from any illness